Age-related normative changes in cerebral perfusion: data from The Irish Longitudinal Study on Ageing (TILDA) - Knight, Silvin; Kenny, Rose; Mc Morrow, Jason; Newman, Louise; Meaney, James; Williamson, Wilby (My University, 2021)
Objective: To establish normative reference values for total grey matter cerebral blood flow (CBFGM) measured using pseudo-continuous arterial spin labelling (pCASL) MRI in a large cohort of community-dwelling adults aged 54 years and older. Background: Quantitative assessment of CBFGM may provide an imaging biomarker for the early detection of those at risk of neurodegenerative diseases, such as Alzheimer's and dementia. However, the use of this method to differentiate normal age-related decline in CBFGM from pathological reduction has been hampered by the lack of reference values for cerebral perfusion. Methods: The study cohort comprised a subset of wave 3 (2014-2015) participants from The Irish Longitudinal Study on Ageing (TILDA), a large-scale prospective cohort study of individuals aged 50 and over. Of 4,309 participants attending for health centre assessment, 578 individuals returned for 3T multi-parametric MRI brain examinations. In total, CBFGM data acquired from 468 subjects using pCASL-MRI were included in this analysis. Normative values were estimated using Generalised Additive Models for Location Shape and Scale (GAMLSS) and are presented as percentiles, means and standard deviations. Results: The mean age of the cohort was 68.2 ± 6.9 years and 51.7% were female. Mean CBFGM for the cohort was 36.5 ± 8.2 ml/100g/min. CBFGM decreased by 0.2 ml/100g/min for each year increase in age (95% CI =-0.3,-0.1; p ≤ 0.001) and was 3.1 ml/100g/min higher in females (95% CI = 1.6, 4.5; p ≤ 0.001).
PUBLISHED
Keywords: Cerebral blood flow; Cerebral perfusion; Arterial spin labelling magnetic resonance imaging; ASL MRI; Ageing; Normative values; Ageing